2013
DOI: 10.1371/journal.pone.0062228
|View full text |Cite|
|
Sign up to set email alerts
|

Embodied Greenhouse Gas Emissions in Diets

Abstract: Changing food consumption patterns and associated greenhouse gas (GHG) emissions have been a matter of scientific debate for decades. The agricultural sector is one of the major GHG emitters and thus holds a large potential for climate change mitigation through optimal management and dietary changes. We assess this potential, project emissions, and investigate dietary patterns and their changes globally on a per country basis between 1961 and 2007. Sixteen representative and spatially differentiated patterns w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
124
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(130 citation statements)
references
References 37 publications
4
124
1
1
Order By: Relevance
“…Moreover, the importance of crop commodities in food supplies, particularly in contribution to protein and fat, may shift in response to health, natural resources, and climate pressures (22,(57)(58)(59), counteracting the trend demonstrated over the past 50 y in increased animal as well as energy-dense plant food commodity consumption. The trajectory of northern European food supplies appears to be demonstrating such a trend (22).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the importance of crop commodities in food supplies, particularly in contribution to protein and fat, may shift in response to health, natural resources, and climate pressures (22,(57)(58)(59), counteracting the trend demonstrated over the past 50 y in increased animal as well as energy-dense plant food commodity consumption. The trajectory of northern European food supplies appears to be demonstrating such a trend (22).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that dietary patterns globally are changing from low to high calorie intakes [65], and this leads to increased consumption of vegetables compared to cereals. Between 2000 and 2013, the annual cereal consumption of Chinese residents increased by 19.75%, while that of vegetables increased by 48.43% [66], a trend that is projected to continue.…”
Section: Discussionmentioning
confidence: 99%
“…Even today, Indonesia is a net importer of food, and malnutrition and stunting among children is present (WFP, 2012). With increasing development and higher demand lifestyles, the water intensity of food-consumption patterns may increase, further exacerbating the problem (Pradhan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%